Effects of Gold Colloids on the Photosensitization Efficiency of Silica Particles Doped with Protoporphyrin IX. Issue 12 (12th October 2017) - Zampini, Giulia; Tarpani, Luigi; Massaro, Giuseppina; Gambucci, Marta; Nicoziani, Andrea; Latterini, Loredana
Abstract: Photodynamic treatments represent a non‐invasive tool to intervene in the cell cycle, only when needed, but high excitation power is an important limitation. In this work, protoporphyrin IX (PpIX) is covalently anchored to the surface of silica particles. The hybrid colloids are prepared with different photosensitizer loadings and characterized by TEM, SEM‐EDX and spectroscopic methods. The visible excitation of the colloidal samples generates reactive oxygen species, which are quantified by use of a specific chemical scavenger agent (1, 3‐diphenylisobenzofuran). The determined efficiencies depend on the PpIX loading, being higher in the sample where the aggregation is reduced. To enhance further the photosensitizing performance of silica‐PpIX samples, increasing amounts of gold nanoparticles are conjugated to the silica surface in order to exploit the antenna effect of plasmonic nanostructures. The visible excitation of silica‐PpIX systems in the presence of gold nanoparticles results in a faster and more efficient photoinduced formation of ROS species reaching a 230 % enhancement of ROS photosensitization when 10 13 Au nanoparticles mL −1 (corresponding to circa 75 ppm of gold) are present. The efficiency data are discussed in terms of plasmonic enhancement of the excitation field. Abstract : The golden touch : The performances of silica particles doped with protoporphyrin IX (silica‐PpIX) in photosensitizing reactive oxygen species (ROS) are enhanced by conjugation of gold nanoparticles to the silica surface. The antenna effect is strongly dependent on the concentration of plasmonic nanostructures. A 230 % enhancement of ROS photosensitization is achieved when only 10 13 Au nanoparticles mL −1 are present.